PROFILE CHARACTERISTICS OF THE RESPONDENTS SELECTED TO STUDY THE RASTRIYA KRISHI VIKAS YOJANA PROGARMME IN TELANGANA STATE - and D. SRINIVASA CHARY, B. RAJASHEKAR, V. SUDHA RANI, I. SREENIVASA RAO, G.E.CH. VIDYASAGAR (The Journal of Research, PJTSAU, 2021)
A study was conducted to know the profile characteristics of the respondents selected to study the RKVY programme in Telangana state. Three districts were selected randomly i.e Adilabad district from Northern Telangana Zone, Mahaboobnagar district form Southern Telangana Zone and Warangal urban district from Central Telangana Zone. From each district 80 respondentsfrom agriculture and allied sectors were selected. A total of 240 respondents selected randomly. Profile characteristics selected for the study are age, education, farm size, farming experience, trainings received, extension contact, information seeking behaviour, farm mechanization status, risk orientation, innovativeness, socio political participation, achievement motivation and subsidy orientation. Exploratory research design was followed in the study, Majority of the respondents had middle age (55.00%),educated upto primary school (46.25%), had small farm size (37.92%), possessed medium farming experience (45.41%), received medium level of training (40.41%), had medium level of extension contact (52.50%), information seeking behaviour (40.42%), farm mechanization status (53.34%), risk orientation (59.58%), achievement motivation (41.66%), high level of innovativeness (52.09%), subsidy orientation (47.08%) and had low level of socio-political participation (45.00%).